2010
DOI: 10.4045/tidsskr.09.0796
|View full text |Cite
|
Sign up to set email alerts
|

Alvorlig skadede overført til universitetssykehus

Abstract: Trauma care at local hospitals may be improved by more systematic imaging, a lower threshold for emergency surgery, and early communication with the university hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
3
0
5
Order By: Relevance
“…Local hospitals in Finnmark have improved in-house trauma care by the regular multiprofessional trauma team training that seems to even out differences between urban and rural care [20]. Still, studies from Northern Norway have shown areas of potential improvement in local hospital trauma management concerning transfer routines, damage-control surgery, and use of diagnostic imaging [21,22]. These conditions are not exclusive to Finnmark, indicating that distance in itself probably plays a part in the disadvantages of the most rural trauma victims.…”
Section: Discussionmentioning
confidence: 99%
“…Local hospitals in Finnmark have improved in-house trauma care by the regular multiprofessional trauma team training that seems to even out differences between urban and rural care [20]. Still, studies from Northern Norway have shown areas of potential improvement in local hospital trauma management concerning transfer routines, damage-control surgery, and use of diagnostic imaging [21,22]. These conditions are not exclusive to Finnmark, indicating that distance in itself probably plays a part in the disadvantages of the most rural trauma victims.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, transferred patients are included in our analysis. We have previously shown that many trauma patients transferred in the acute phase are not adequately diagnosed and stabilized [18]. Minimization of undertriage requires decision-makers to strictly comply with our TTA protocol in all trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some Scandinavian regions, the distance between the injury location and the nearest regional trauma centre may be great, and prehospital transport is often influenced by weather and topographical considerations [15,16]. This increases the role of local hospitals in resuscitating, stabilising and promptly transferring severely injured patients to higher levels of care [11]. The optimal time range for direct trauma centre admission vs. initial stabilisation at local hospitals is, however, yet to be determined.…”
Section: Introductionmentioning
confidence: 99%